Resonance Frequency Analysis and Oral Implant Stability: A Long Term Relationship - Prachi Khuntia1 , Rashmita Nayak2, Abhaya Chandra Das3, Rinkee Mohanty4 , Anurag Satpathy2 , Sharmis (Indian Journal of Forensic Medicine & Toxicology, 2020)
For a desired osseointegration to take place, implant stability plays an expository role. Hence to achievea functional dental implant, successful osseointegration is a necessity. The two major factors affect thesurvival of implants that is the stability of the implant during placement and the event of osseointegration.Two separate phases determine the stability of implant: Primary implant stability as well as secondaryimplant stability. Mechanical grip withthe cortical bone determines the primary stability whereas Secondarystability is due to regeneration as well asremodelling of the surrounding bone and surrounding tissue aroundthe implant after loading. Implant stability is a mechanical phenomenon which is in association with localfactors such as quality of bone, type of placement technique used, quantity and the type of implant used. It isconsidered highly advisable for implementation of a user-friendly, non-invasive, clinically reliable methodto assess the stability of the implant and the osseointegration process. Resonance frequency analysis (RFA)is one of the method thats how almost perfect consistency after statistical analysis. Therefore, the focus ofthis currentre view article is particularly on presently used RFA method which are highly followed in thecurrent times to elicit oral implant stability.